Signing of letter of intent (LOI) between FIST, UMP, FRIM and TPM - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
OCT 12, MARAN: To strengthen research collaboration on herbs in Malaysia, the Faculty of Industrial Sciences & Technology (FIST), Universiti Malaysia Pahang (UMP) has signed a Letter of Intent (LOI) with Forest Research Institute Malaysia (FRIM) and TPM Biotech Sdn. Bhd. at the FR IM station in Kampung Ulu Luit, Maran.